Approach to fragmented central venous catheters - YILDIZELİ, BEDRETTİN; BALTACIOĞLU, FEYYAZ; BATIREL, HASAN FEVZİ (SAGE PUBLICATIONS LTD, 2005)
Prolonged venous access devices are needed in cancer patients for central venous access. Catheter fragmentation leading to catheter malfunction represents a rare problem. Herein we present our experience in the management of fragmented catheters. Between 2001 and 2003, 183 catheters were placed via the subdavian vein, and five cases of fragmented catheters were observed. Fragments were removed by an Amplatz gooseneck snare (Microvena, St. Paul, MN) with angiographic intervention. The diagnosis of the breakage was made by chest radiography.The incidence of catheter breakage was 2.7%. All fragments were removed by the snare, without any complications. Catheter narrowing and breakage owing to its medial positioning in the subdavian vein were the main causes of catheter malfunction. In any case of catheter malfunction, radiologic evaluation of the catheter must be done to rule out its rupture. Removal of the fragments using the Amplatz snare is a safe and easily applied procedure.
Keywords: Amplatz gooseneck snare; complications; prolonged venous access devices; SUBCLAVIAN VEIN CATHETERIZATION; ACCESS DEVICES; COMPLICATIONS; PORTS; SNARE